Wrox Press Announces the Staging of Its First ASP Professional Web Developers Conference (PR Newswire, 1999)
Wrox Washington '99 embodies the Wrox Programmer to Programmer(TM) philosophy. It brings together a combination of recognized industry professionals, Web solution providers, Microsoft product developers, and Wrox authors and technical reviewers to present up to the minute briefings on XML and ASP with related technologies (ADO, RDS, MTS, MSMQ, ADSI, Site Sever).